(untitled) (Journal of Hama University, 2020)
Samples of Chironominae larvae and Mollusks were collected from Balloran and Seryscia rivers junction station since December 2017 till May 2019. Three genres belong to Chironominae (Chironomus, Apedilum, Microtendipies), five species belong to chironomus: Chironomus plumosus, Ch. riparious, Ch. stigmaterus, Ch. austini Ch. dorsalis and Apedilum elachistus belong to the second were identified. The last two genres and the last species were recorded for the first time in Syria. Also 5 species of Mollusca were identified for the first time in this station ( Melanopsis praemorsa, Physa acuta, Physa phontinalis, Planorbis. umbilicatus, Sphaerum lacustre). Physical and chemical properties of water were studied and the results were diagrammed. Some of biocenose characteristics were studied.